Effect of foliar application of micronutrients and urea on mungbean varieties - Sanjida, Israt Jahan; Munan, Md Mohaiminul Islam; Hossain, Iqbal; Saimon, Abdur Rahman; Jahan, Mst. Nusrat; Noor e Jannat, Syeda (Canadian Journal of Agriculture and Crops, 2023)
Experiment was carried out to at the Agronomy field of Patuakhali Science and Technology University (PSTU). The treatments comprised of four variety and three fertilizer including control. Varieties were V1= BINA Mung-8, V2=BARI mung-2, V3=BARI mung-5 and V4=BARI mung-6 and treatments were T0 = control, T1 =micro nutrient, T2= micronutrient and urea. The experiment was laid-out in the Randomized Complete Block Design (RCBD) with three replications. The maximum plant height was found at BARI mung-6 (29.7). Maximum nodule number was found at BARI mung-6 variety (5.90). The number of effective nodule was highest at BARI mung-6 variety (2.36). In case of no of seed per pod and 1000-seed weight, BARI mung-6 variety gave highest value and those were 11.25 and 70.5 g respectively. Maximum plant height, nodule number, number of effective nodule and number of pod per plant were found at T2 treatment. The pod length, seed per pod and 1000-seed; T2 treatment gave the highest value and those were 5.5 cm, 11.25 and 65.64 g respectively. In case of plant height, chlorophyll content, number of nodule, number of effective nodule, pod per plant, pod length, pod weight/m2, seed per pod and 1000-seed weight, combined effecr of BARI mung-6 x micronutrient and urea (T2) gave highest value and those were (29.95, 47.5, 6.17, 2.40, 6.20, 6.20, 76.75, 11.20) cm and 68.45 g respectively. This result revealed that mungbean variety BARI mung-6 and T2 treatment performed best in combination (V4T2).